2007
DOI: 10.4049/jimmunol.178.5.3126
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN Signaling Is Crucial for Host Resistance against Different Species of Pathogenic Bacteria

Abstract: It is known that host cells can produce type I IFNs (IFN-αβ) after exposure to conserved bacterial products, but the functional consequences of such responses on the outcome of bacterial infections are incompletely understood. We show in this study that IFN-αβ signaling is crucial for host defenses against different bacteria, including group B streptococci (GBS), pneumococci, and Escherichia coli. In response to GBS challenge, most mice lacking either the IFN-αβR or IFN-β died from unrestrained bacteremia, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
217
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(230 citation statements)
references
References 53 publications
12
217
1
Order By: Relevance
“…When examining the role for IFNAR in IL-12 and TNF-␣ secretion, we observed that in both cases IFNAR and, by inference, type I IFNs were required for high- level secretion of these cytokines. This observation is supported by other studies which suggest that simultaneous activation of both STAT1 and NF-B is important in the priming of IL-12 production in DCs (54) and that TNF-␣ secretion can be influenced by type I IFN secretion (32). Finally IL-1␤, an important mediator in the inflammatory response and a downstream indicator of inflammasome activation (37), was produced exclusively in GM-CSF-expanded DCs although when cDCs were sorted and concentrated from FL-expanded cultures, they, too, were also able to produce IL-1␤, albeit at low levels.…”
Section: Discussionsupporting
confidence: 84%
“…When examining the role for IFNAR in IL-12 and TNF-␣ secretion, we observed that in both cases IFNAR and, by inference, type I IFNs were required for high- level secretion of these cytokines. This observation is supported by other studies which suggest that simultaneous activation of both STAT1 and NF-B is important in the priming of IL-12 production in DCs (54) and that TNF-␣ secretion can be influenced by type I IFN secretion (32). Finally IL-1␤, an important mediator in the inflammatory response and a downstream indicator of inflammasome activation (37), was produced exclusively in GM-CSF-expanded DCs although when cDCs were sorted and concentrated from FL-expanded cultures, they, too, were also able to produce IL-1␤, albeit at low levels.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, any excesses or deregulation leading to an imbalance in these sets of responses may spell doom to the host. In this regard, although type I IFNs were found to play a protective role during some bacterial infections (16), recent findings suggest that strong type I IFN responses not only result in increased susceptibility to bacterial infections (10)(11)(12)(13)(14) but also are a central pathologic event in sepsis and other hyperinflammatory conditions associated with bacterial infections (2,15).…”
Section: Discussionmentioning
confidence: 99%
“…41: 1969-1979 Immunity to infection previously [14]. Primers and TaqMan MGB probes for the above cytokines have been described previously [14] and were purchased from Applied Biosystems. PCR conditions were as follows: 951C, 10 min; (951C, 15 s; 601C, 1 min) Â 40 cycles.…”
mentioning
confidence: 99%
“…Real-time PCR data were normalized in each individual sample by the level of b-actin expression. Gene expression was measured by the comparative C T method (DDC T ) and was reported as the n-fold difference relative to the normalized expression of unstimulated samples [14]. …”
mentioning
confidence: 99%